2006
DOI: 10.1021/la052652c
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Gold Nanoparticles Synthesized by Filamentous Cyanobacteria from Gold(I)−Thiosulfate and Gold(III)−Chloride Complexes

Abstract: Plectonema boryanum UTEX 485, a filamentous cyanobacterium, has been reacted with aqueous Au(S(2)O(3))(2)(3)(-) and AuCl(4)(-) solutions ( approximately 400-550 mg/L Au) at 25-100 degrees C for up to 1 month and at 200 degrees C for 1 day. The interaction of cyanobacteria with aqueous Au(S(2)O(3))(2)(3)(-) promoted the precipitation of cubic (100) gold nanoparticles (<10-25 nm) at membrane vesicles and admixed with gold sulfide within cells and encrusted on the cyanobacteria, whereas reaction with AuCl(4)(-) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(114 citation statements)
references
References 47 publications
5
108
1
Order By: Relevance
“…Oat (Avena sativa) biomass was also found to recover Au (III) ions from aqueous solutions and reduce Au (III) to Au (0), forming Au nanoparticles (Armendariz et al, 2004(Armendariz et al, , 2009). Synthesis of nanogold has also been reported in algae, including Chlorella vulgaris (Ting et al, 1995), Sargassum wightii (Singaravelu et al, 2007) and Plectonema boryanum (Lengke et al, 2006a(Lengke et al, , 2006b). Gold nanoparticle synthesis by cyanobacteria (such as Lyngbya majuscula and Spirulina subsalsa), green algae (Rhizoclonium hieroglyphicum and R. riparium) and diatoms (Nitzschia obtusa and Navicula minima) has recently been reported by Chakraborty et al (2006Chakraborty et al ( , 2009 and Nayak et al (2006), and biosynthesis of gold nanorods by Nostoc ellipsosporum by Parial et al (2012).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Oat (Avena sativa) biomass was also found to recover Au (III) ions from aqueous solutions and reduce Au (III) to Au (0), forming Au nanoparticles (Armendariz et al, 2004(Armendariz et al, , 2009). Synthesis of nanogold has also been reported in algae, including Chlorella vulgaris (Ting et al, 1995), Sargassum wightii (Singaravelu et al, 2007) and Plectonema boryanum (Lengke et al, 2006a(Lengke et al, , 2006b). Gold nanoparticle synthesis by cyanobacteria (such as Lyngbya majuscula and Spirulina subsalsa), green algae (Rhizoclonium hieroglyphicum and R. riparium) and diatoms (Nitzschia obtusa and Navicula minima) has recently been reported by Chakraborty et al (2006Chakraborty et al ( , 2009 and Nayak et al (2006), and biosynthesis of gold nanorods by Nostoc ellipsosporum by Parial et al (2012).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, second generation nanotechnology is focused towards clean technologies that minimize possible environmental and human health risks associated with manufacture and fabrication; there is an ever-growing demand for development of clean, nontoxic, and environmentally benign synthesis procedures. Microorganisms, including bacteria, fungi and algae, have been proposed as potential eco-friendly nano-factories for the synthesis of metal, including gold, nanoparticles (Nair & Pradeep, 2002;Lin et al, 2005;Lengke et al, 2006aLengke et al, , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of incubation temperature for maximum gold nanoparticles synthesis was studied at a temperature range of 10-50 o C +using nutrient broth and optimum temperature of 37 o C leading to maximum gold nanoparticles synthesis was observed (Figure 5c). It has also been reported that incubation time for maximum gold nanoparticles formation ranges from 30 to 37 o C (Lengke et al, 2006). Effect of different wavelengths for the maximum optical density values of gold nanoparticles synthesis was investigated in the range of 400-650 nm and an optimum wavelength of 560 nm was found to be leading to maximum values of optical density of gold nanoparticles synthesis (Figure 5d).…”
Section: Optimization Of Culture Conditions For Maximum Gold Nanopartmentioning
confidence: 67%
“…In vitro studies have shown that bacteria are able to immobilize and/or precipitate gold from gold-rich solutions [13][14][15][16]. Kenney et al [17] noted that non-metabolizing bacteria were also able to remove gold from aqueous gold solutions.…”
Section: Introductionmentioning
confidence: 99%